KEBEBASAN DAN KESADARAN DALAM NOVEL “SANG ALKEMIS” KARYA PAULO COELHO (EKSISTENSIALISME JEAN PAUL SARTRE) - Alpino; Kafrawi, M (Jurnal Ilmu Budaya, 2023)
This research is entitled Freedom and Consciousness in the Novel “The Alchemist” by Paulo Coelho (Existentialism study of Jean Paul Sartre). The problem that will be examined in this study is the freedom that focuses on the main character in this novel. The purpose of this study is to describe the form of Sartre’s existentialism towards the main character. The technique used in this study is the technique of reading and note taking with a intellectual and hermeneutic approach. The result of this reasearch shows that the main character in this novel, is someone who has a tendency to be reflective and authentic.